Adoption of the transradial approach for percutaneous coronary intervention and rates of vascular complications following transfemoral procedures: Insights from NCDR. Issue 5 (23rd January 2018) - Badri, Marwan; Shapiro, Timothy; Wang, Yongfei; Minges, Karl E.; Curtis, Jeptha P.; Gray, William A.
Abstract: Objectives: This study was designed to examine the association between adopting the transradial approach for percutaneous coronary intervention (PCI) and rates of vascular complications following transfemoral PCI. Background: Recent studies raised concerns that operators adopting the transradial approach may lose their transfemoral access skills and experience increased rates of vascular complications. Methods: Retrospective analysis of data from the NCDR CathPCI Registry to examine the rates of vascular complications among physicians who were femoral operators (>90% of cases) in 2010–2011 and later adopted the transradial approach to PCI among low‐, intermediate‐, or high‐level adopters (≤33%, 34–66%, and >66%, respectively) in 2014–2015. Propensity score matching was used to control for confounding factors. Results: A total of 1, 704, 708 procedures performed by 4, 697 operators were included. Most operators were low‐level adopters (80.7%), followed by intermediate (15.7) and high‐level adopters (3.6%). Compared to the preadoption period, vascular complications of transfemoral PCIs following transradial adoption increased among low‐level adopters (1.29%–1.59%, adjusted OR [95% CI]: 1.24[1.20–1.28], P < 0.001), intermediate‐level adopters (1.37%–1.92%, adjusted OR 1.40[1.29–1.53], P < 0.001), and high‐level adopters (1.54%–1.93%, adjusted OR 1.26[1.00–1.58], P = 0.053).In the post‐adoption period, there was increase in access site bleeding that is likely due to change in registry definition. There was no increase in hematomas, retroperitoneal bleeding or other vascular complications. Conclusions: Adoption of the transradial approach for PCI is not associated with clinically meaningful increase in rates of vascular complications of transfemoral PCIs.